(untitled) (Palíndromo, 2017)
With a poetic trajectory intertwined with the idea of fable, Francis Alÿs de-velops actions that leave practically no material traces. His works have as start-ing point daily situations where the art-ist inserts new narratives, enabling per-ceptions and inaugural perspectives on certain contexts. This article seeks to es-tablish relationships between the fables created by Alÿs and their contributions to our discourses and practices in border-line or marginal situations, both between territories and between daily urban prac-tices.